Spatial consequences of bridging the saccadic gap - Yarrow, Kielan (2005)
We report six experiments suggesting that conscious perception is actively redrafted to take account of events both before and after the event that is reported. When observers saccade to a stationary object they overestimate its duration, as if the brain were filling in the saccadic gap with the post-saccadic image. We first demonstrate that this illusion holds for moving objects, implying that the perception of time, velocity, and distance traveled become discrepant. We then show that this discrepancy is partially resolved up to 500 ms after a saccade: the perceived offset position of a post-saccadic moving stimulus shows a greater forward mislocalization when pursued after a saccade than during pursuit alone. These data are consistent with the idea that the temporal bias is resolved by the subsequent spatial adjustment to provide a percept that is coherent in its gist but inconsistent in its detail.